Handbook of biochemistry and molecular biology - Lundblad, Roger L.; Macdonald, Fiona; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
Edited by renowned protein scientist and bestselling author Roger L. Lundblad, with the assistance of Fiona M. Macdonald of CRC Press, this fifth edition of the?Handbook of Biochemistry and Molecular Biology?gathers a wealth of information not easily obtained, including information not found on the web.Chromatographic methods and solventsClick ChemistryGene EditingMatrix MetalloproteinasesNew tables for this edition: Partial volumes of amino acidsPresented in an organized, concise, and simple-to-use format, this popular reference allows quick access to the most frequently used data. Covering a wide range of topics, from classical biochemistry to proteomics and genomics, it also details the properties of commonly used biochemicals, laboratory solvents, and reagents. An entirely new section on Chemical Biology and Drug Design gathers data on amino acid antagonists, click chemistry, plus glossaries for computational drug design and medicinal chemistry. Each table is exhaustively referenced, giving the user a quick entry point into the primary literature.Protein spectroscopy.
Includes bibliographical references and index.
Also available in print format.
Keywords: Biochemistry; Biotechnology; Molecular biology; SCIENCE / Life Sciences / Biochemistry; SCIENCE / Life Sciences / Biology / Molecular Biology; MEDICAL / Biotechnology; Electronic books